PERANCANGAN APLIKASI POINT OF SALES (POS) BERBASIS WEB MENGGUNAKAN METODE SIKLUS HIDUP PENGEMBANGAN SISTEM - Fitri Marisa; Titania Grawidi Yuarita (Jurnal Teknologi dan Manajemen Informatika, 2017)
The development of information technology is utilized in the field of industry. As the new company is expanding, utilizing point of sale information technology. So that the company does not experience a decline in its production and can continue to compete in the business world. Objectives to be achieved is the analysis and design of point of sale applications to minimize error information in the inventory, sales and profit and loss calculations company. This application is developed by using PHP programming language and MySql database. The result of this research is a structured application designed to process sales data.DOI: https://doi.org/10.26905/jtmi.v3i2.1514